RECONSTRUCTION OF EDUCATION IN THE PERSPECTIVE OF IMAM AL-GHAZALI - Hamida Olfah (CV. ADIBA AISHA AMIRA, 2022)
This paper aims to present the educational thoughts of Imam al- Ghazali in contemporary Islamic education. Al-Ghazali's educational thoughts can be used as inspiration in upholding quality Indonesian education. The concept of al-Ghazali's educational thought is religious-ethical. Al-Ghazali's educational goals cover three aspects, namely cognitive, affective, and psychomotor aspects. In addition to placing two important things as an educational orientation, namely achieving human perfection to qualitatively get closer to Allah SWT; and achieve human perfection to achieve happiness in this world and the hereafter. Educators are individuals who master a scientific discipline and are able to practice it as well as human figures who totally concentrate on the field of education. Students are placed as objects as well as subjects and set ideal criteria that students must strive for in order to be successful in education. Al-Ghazali mentions four categories of scientific classification, namely; classification of syar'iyah (religious) science and 'aqliyah (reasoning); theoretical and practical science. Al-Ghazali's teaching method emphasizes that teachers who provide knowledge are required to use exemplary methods and dialogue in the learning process